onospheric Effects on GPS Signal in Low-Latitude Region : A Case Study Review of South East Asia and Africa - Kismet, Hong Ping; Ibrahim, Abba; Thelaha, Hj Masri; Wan Azlan, Wan Zainal Abidin; Muhammad, M.S.; Bong, Voon Pai (African Journals Online (AJOL), 2015)
The ionosphere is a significant source of errors affecting L- fecting L-Band (1 Band (1 Band (1-2 GHz) signal propagation using Global Position 2 GHz) signal propagation using Global Position System (GPS). The propagated GPS signals that passes through the Earth’s atmosphere where affected by ionosphere ionosphere and troposphere irregularities and caused the signal propagation delay. However, the velocity of signals that propagate within the atmosphere deviates from vacuum line of sight (LOS), while the refractivity of ionosphere and troposphere influence the signal propagation delay troposphere influence the signal propagation delay causing atmospheric effect causing atmospheric effects due to high electrons d s due to high electrons density. Both ensity. Both affect the signal in different ways due to their particular refractive properties. The review focuses of some of the previous research studies conducted on empirical mo previous research studies conducted on empirical modeling of the ionospheric effect in low latitude deling of the ionospheric effect in low latitude region. The gion. The tabulated findings of such models presented in this article. article.